Bio-Oil dari Limbah Padat Sawit dengan Metoda Pirolisa - Saputra, Edy; Bahri, Syaiful (Jurnal Natur Indonesia, 2009)
Bio oil is most important alternative energy resources for human life due to the production of fossil fuel tend todecline. Numbers of researches have been developed on alternative energy resources, such as the conversion ofbiomass. The palm solid waste which is consisted of wood, stem and empty bunch having size of diameter in rangeof 2 to 10 mesh were used in this work. The pyrolysis method is selected in this research. This process was donein stainless steel reactor having length and length of 60.0 and 3.81 cm respectively at temperature of 450 to 600oCunder nitrogen flow. Gas chromatography HP 5890 is utilized to analyze of the bio oil result. The result achieved thehighest yield at 500oC and particle diameter of 2-6 mesh.